2008
DOI: 10.1073/pnas.0802518105
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa benefits fromMedicago truncatula: TheRCT1gene fromM. truncatulaconfers broad-spectrum resistance to anthracnose in alfalfa

Abstract: Alfalfa is economically the most important forage legume worldwide. A recurrent challenge to alfalfa production is the significant yield loss caused by disease. Although knowledge of molecular mechanisms underlying host resistance should facilitate the genetic improvement of alfalfa, the acquisition of such knowledge is hampered by alfalfa's tetrasomic inheritance and outcrossing nature. However, alfalfa is congeneric with the reference legume Medicago truncatula, providing an opportunity to use M. truncatula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 43 publications
1
96
0
Order By: Relevance
“…Furthermore, several studies have focused on direct crop improvement in legume species based on information from well-studied plants. For example, Kwak et al (2008) identified candidate genes responsible for determinacy and photoperiod Sensitivity traits in common bean (P. vulgaris) using homologs in Arabidopsis thaliana floral regulatory genes,and Yang et al (2008) identified a putative resistance gene in alfalfa (M. sativa) based on map-based cloning of RCT1, a host resistance (R) gene in M. truncatula, which conferred resistance in alfalfa cultivars. Multiple-legume species macro synteny comparisons were also performed between cowpea and soybean,and cowpea and M. truncatula, based on the genetic map of cowpea.The availability of genome sequences across legume species including M. Truncatula (Young et al, 2011), Lotus japonicas (Sato et al, 2008), soybean (Schmutz et al,2010), pigeonpea (Varshney et al,2012), chickpea (Varshney et al,2013), mungbean , commonbean (Schmutz et al,2014), and adzuki bean (Kang et al,2015) have enabled extensive comparative genomics across species, including genomic contents and gene orders.…”
Section: Advancements In Next-generation Sequencing (Ngs)mentioning
confidence: 99%
“…Furthermore, several studies have focused on direct crop improvement in legume species based on information from well-studied plants. For example, Kwak et al (2008) identified candidate genes responsible for determinacy and photoperiod Sensitivity traits in common bean (P. vulgaris) using homologs in Arabidopsis thaliana floral regulatory genes,and Yang et al (2008) identified a putative resistance gene in alfalfa (M. sativa) based on map-based cloning of RCT1, a host resistance (R) gene in M. truncatula, which conferred resistance in alfalfa cultivars. Multiple-legume species macro synteny comparisons were also performed between cowpea and soybean,and cowpea and M. truncatula, based on the genetic map of cowpea.The availability of genome sequences across legume species including M. Truncatula (Young et al, 2011), Lotus japonicas (Sato et al, 2008), soybean (Schmutz et al,2010), pigeonpea (Varshney et al,2012), chickpea (Varshney et al,2013), mungbean , commonbean (Schmutz et al,2014), and adzuki bean (Kang et al,2015) have enabled extensive comparative genomics across species, including genomic contents and gene orders.…”
Section: Advancements In Next-generation Sequencing (Ngs)mentioning
confidence: 99%
“…A major gene (RCT1) conferring resistance to anthracnose in alfalfa has been cloned in M. truncatula [80]. Similarly, QTL for resistance to A. euteiches [81,82], spring black stem and leaf spot [83] have been mapped in M. truncatula, but no verification of resistance in alfalfa has been documented.…”
Section: Characteristics Of Alfalfa Genetic Linkage Mapsmentioning
confidence: 99%
“…First, Yang et al (2008) reported the use of barrel medic to map-base clone the RCT1 gene that confers resistance to multiple races of anthracnose (Colletotrichum trifolii) in alfalfa (Medicago sativa). This nicely illustrates the use of a model to investigate a trait that would be difficult to dissect genetically in alfalfa, which is tetraploid and predominantly outcrossing.…”
Section: Translational Genomics In the Legumesmentioning
confidence: 99%
“…Barrel medic has been used for study of phenylpropanoid and isoflavonoid pathways and secondary metabolites (Farag et al, 2008), various defense responses (Yang et al, 2008), root architecture (Gonzalez-Rizzo et al, 2006), and aluminum tolerance (Chandran et al, 2008). Soybean has been a model for studies of seed development (for review, see Vodkin et al, 2008), root hair development and early nodulation responses, mineral uptake, and protein and oil biosynthesis.…”
Section: Many Models In the Legumesmentioning
confidence: 99%